Habib Tanvir : - Katyal, Anjum (SAGE Publications, 2012)
"Habib Tanvir (1923-2009), playwright, director, actor, journalist, critic, is probably best known for his most popular play, Charandas Chor (1974). However, his real significance in the history of post-independence Indian theatre is that he signposted an important path for the development of modern theatre in India. His productions with Naya Theatre using Chhatisgarhi folk actors opened up a new direction on the map of theatre in India He pioneered an alternative to the dichotomy between the 'theatre of roots' movement (which turned to the Sanskrit Natyashastra and regional performance forms for content, style, training and form) and western-influenced, realist urban theatre styles. His was an inclusive approach to modern theatre which had the space in it for folk actors, who brought with them a whole culture and aesthetic rapidly being marginalized by mainstream theatre in India. His was neither folk theatre nor theatre of roots; neither revisionist nor revivalist; nor could it be classified as realism or naturalism. Neither was it exotic 'ethnic spectacle' like that of some of his peers. His was a serious exploration of how one could do modern theatre integrated with age-old - and yet equally contemporary - folk culture on a basis of equality. This study of Habib Tanvir will analyse his theatre and its contribution to Indian theatre history. Starting with his early life and preparation for his life's work, it will look at his professional trajectory from Agra Bazaar to Gaon Ka Naam Sasural, when he was experimenting and searching for his true form; to Charandas Chor, which expressed the full flowering of his mature style; thereafter the book will explore various important aspects of his theatre philosophy and practice as he experimented with content rather than form."--Provided by publisher.